Os cursos de licenciatura em Matemática no estado de Rondônia : um panorama histórico - Ruezzene, Gilcimar Bermond (2012)
Describe and analyze the creation, expansion and consolidation processes of graduation courses in Mathematics in the Rondônia State is the central objective of this research. From this perspective, we propose to present in summary form the extinct courses that enabled teachers to teach mathematics in Rondonia; to map the Mathematics courses in the State of Rondônia; to describe and analyze the processes that led to the creation of Mathematics courses in operation, as well as to characterize some changes and permanence in their Pedagogical Projects. This research is based in the investigation about the History of Mathematics Education in Brazil. To develop this research we analyzed write, iconographic and oral historical sources, found in archives of institutions of higher education in Rondônia, personal files and by interviews. In the interaction of these sources, we sought to build a history with the theoretical assumptions of Peter Burke and Jacques Le Goff, among other authors as a guide. It was the constant exercise of search and interpretation in these sources that permit (re) construct elements of the trajectory in the Bachelor Degree in Mathematics in Rondônia. It was observed that the trajectory of the investigated courses is characterized by political intentions, not always clear, difficulties in physical, structural, social value and human resources, which show a developing region with specific needs Changes in curricular courses, almost entirely, only sought to attend a teacher training law in ample and general way. It’s recorded, thus, a dynamic history that articulates with the Rondônia State history and with the institutions where these courses are created, which receives and exerts internal and external influences from others institutions and political and economic contexts.